Structural and ionic conductivity studies of PVA/PVP: KNO3 composite polymer electrolyte films. (2018) - Rao, M.C.; Srinivasa Rao, Ch.; Srikumar, T.
Abstract: Composite polymer electrolytes films were prepared with potassium nitrate (KNO3 ) in PVA/PVP blend polymers with different wt% compositional ratios by solution cast technique. XRD revealed that the structural phase of the film decreases with increasing wt% of the salt composition. The chemical complexation and the bond formations between the functional groups were confirmed by FTIR. The ionic conductivity of the prepared solid polymer electrolytes has been measured by AC and DC conductivity plots and the higher ionic conductivity was found to be 1.29x10 -3 S/cm at 373 K for the composition 60PVP/PVA: 40 KNO3 . The transference number revealed that the charge transport occurs in these polymer films was mainly due to ions. Using these prepared composite polymer electrolytes, electrochemical cell was fabricated and the discharge parameters were studied.